2013
DOI: 10.3377/004.048.0211
|View full text |Cite
|
Sign up to set email alerts
|

Orbit Orientation and Eye Morphometrics in Giraffes (Giraffa camelopardalis)

Abstract: Giraffe are thought to have excellent vision. We measured eye size, orbit orientation and retina surface area in 27 giraffes of both sexes ranging in age from neonates to mature adults (>10 yrs), to assess how it changes with growth, whether their eye anatomy correlates with their apparently excellent vision and lifestyle, and we have compared our findings with those for other large mammals to assess whether giraffe eye anatomy is unique. We found that giraffe eye volume increases from 33 cm 3 at birth to appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…Allometry of orbital convergence has rarely been investigated during the growth of a single modern species. In a recent ontogenetic study of giraffes, it was discovered that the amount of binocular overlap increased with age, with adults having less panoramic vision than neonates (Mitchell et al, ). Comparisons across taxa have shown that orbital convergence and skull size are positively correlated in herpestids (Noble et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Allometry of orbital convergence has rarely been investigated during the growth of a single modern species. In a recent ontogenetic study of giraffes, it was discovered that the amount of binocular overlap increased with age, with adults having less panoramic vision than neonates (Mitchell et al, ). Comparisons across taxa have shown that orbital convergence and skull size are positively correlated in herpestids (Noble et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The sender generates a signal which is transmitted through a medium (environment) and detected by a receiver in whom it causes behavioral change (Kaplan, ). The signals through which giraffes are thought to exchange fundamental information are visual, olfactory, or auditory (Bercovitch & Berry, ; Mitchell et al ., ; Dagg, ; Baotic et al ., ). Visual communication entails information exchange based on use of giraffes’ sight.…”
Section: Methodsmentioning
confidence: 99%
“…Comparatively, investigations of giraffe communication have tended to focus on anatomical studies (e.g. eye morphology; Howland, Merola & Basarab, ; Burton, ; Schiviz et al ., ; Mitchell et al ., ; Veilleux & Kirk, ) or genetic analyses (e.g. Ishengoma, Agaba & Cavener, ).…”
Section: Introductionmentioning
confidence: 99%
“…Giraffes are the longest-necked mammals which depend heavily on their eyesight to feed, communicate and avoid predators. Interestingly, Mitchell et al (2013) observed that giraffe features associated with good vision seemed to be correlated with its long neck. In addition to our previous finding of positive selection on PRPH2 and CYP27B1, this study identifies selection divergence in CRYAA and OPN1LW between giraffe and other ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…Vision and ecological studies appear to show that considerable distinction in vision perceptiveness exists between giraffe and other artiodactyls including its close relative, the okapi. Giraffes have excellent aerial vision reinforced by their long necks, which is uniquely the highest among ruminants and predominantly rely on vision communication relative to other senses (Young & Isbell, 1991;Mitchell et al, 2013;VanderWaal et al, 2013;Veilleux & Kirk, 2014). By contrast, okapi have poor eyesight adapted to low-light environment and depend heavily on their smell and hearing acuities to exploit the environment (Lindsey, Green & Bennett, 1999;Greive & Iwago, 2003).…”
Section: Introductionmentioning
confidence: 99%